Regioselective C4 and C6 Double Oxidation of Cellulose by Lytic Polysaccharide Monooxygenases. Issue 2 (18th December 2021) - Sun, Peicheng; Laurent, Christophe V. F. P.; Boerkamp, Vincent J. P.; van Erven, Gijs; Ludwig, Roland; van Berkel, Willem J. H.; Kabel, Mirjam A.
Abstract: Lytic polysaccharide monooxygenases (LPMOs) play a key role in enzymatic degradation of hard‐to‐convert polysaccharides, such as chitin and cellulose. It is widely accepted that LPMOs catalyze a single regioselective oxidation of the C1 or C4 carbon of a glycosidic linkage, after which the destabilized linkage breaks. Here, a series of novel C4/C6 double oxidized cello‐oligosaccharides was discovered. Products were characterized, aided by sodium borodeuteride reduction and hydrophilic interaction chromatography coupled to mass spectrometric analysis. The C4/C6 double oxidized products were generated by C4 and C1/C4 oxidizing LPMOs, but not by C1 oxidizing ones. By performing incubation and reduction in H2 18 O, it was confirmed that the C6 gem ‐diol structure resulted from oxygenation, although oxidation to a C6 aldehyde, followed by hydration to the C6 gem ‐diol, could not be excluded. These findings can be extended to how the reactive LPMO‐cosubstrate complex is positioned towards the substrate. Abstract : Single and double ? Lytic polysaccharide monooxygenases (LPMOs) were reported to form C1/C4 double oxidized cello‐oligosaccharides in addition to C1 or C4 single oxidized ones. Using NaBD4 reduction and HILIC‐ESI‐CID‐MS/MS 2 approach, it is found that C4/C6 double oxidized cello‐oligosaccharides are generated, and not C1/C4 double oxidized products. Experiments in H2 18 O further show that C6 gem ‐diol is formed by an LPMO‐catalyzed reaction.